Strategi Pembelajaran Holistik Berbasis Religious Quotient (RQ) pada Pendidikan Anak Usia Dini: Kajian Teoretis dan Studi Kasus - Afnan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This article examines holistic learning strategies based on Religious Quotient (RQ) as an effort to integrate cognitive, affective, and spiritual aspects in early childhood education. The research employs a descriptive qualitative approach utilizing literature study, document observation, content analysis, and a case study at